Type E Botulinum Neurotoxin-Producing Clostridium butyricum Strains Are Aerotolerant during Vegetative Growth - Serena Camerini (American Society for Microbiology, 2019)
ABSTRACT Clostridium butyricum, the type species of the genus Clostridium, is considered an obligate anaerobe, yet it has been shown to grow in the presence of oxygen. C. butyricum strains atypically producing the botulinum neurotoxin type E are the leading cause of type E human botulism in Italy. Here, we show that type E botulinum neurotoxin-producing C. butyricum strains growing exponentially were able to keep growing and producing toxin in vitro upon exposure to air, although less efficiently than under ideal oxygen-depleted conditions. Bacterial growth in air was maintained when the initial cell density was higher than 103 cells/ml. No spores were detected in the cultures aerated for 5 h. To understand the biological mechanisms allowing the adaptation of vegetative cells of C. butyricum type E to oxygen, we compared the proteome and metabolome profiles of the clostridial cultures grown for 5 h under either aerated or anaerobic conditions. The results indicated that bacterial cells responded to oxygen stress by slowing growth and modulating the expression of proteins involved in carbohydrate uptake and metabolism, redox homeostasis, DNA damage response, and bacterial motility. Moreover, the ratio of acetate to butyrate was significantly higher under aeration. This study demonstrates for the first time that a botulinum neurotoxin-producing Clostridium can withstand oxygen during vegetative growth. IMPORTANCE Botulinum neurotoxins, the causative agents of the potentially fatal disease of botulism, are produced by certain Clostridium strains during vegetative growth, usually in anaerobic environments. Our findings indicate that, contrary to current understanding, the growth of neurotoxigenic C. butyricum strains and botulinum neurotoxin type E production can continue upon transfer from anaerobic to aerated conditions and that adaptation of strains to oxygenated environments requires global changes in proteomic and metabolic profiles. We hypothesize that aerotolerance might constitute an unappreciated factor conferring physiological advantages on some botulinum toxin-producing clostridial strains, allowing them to adapt to otherwise restrictive environments.